Implementación de brazo de reacción para el Torque de Suspensión Trasera de CAT 793. (2022)
The objective of this investigation is the development of a reaction arm for the application of controlled torque in bolts of the rear suspension of the CAT-793 truck, based on the manufacturer's recommendations, modifications to existing tools and the experience of the operators who They are the people who intervene on a daily basis in these teams.